Vitamin D status and childhood health - Youn Ho Shin; Hye Jung Shin; Yong-Jae Lee (Korean Pediatric Society, 2013)
Vitamin D is an essential component of bone and mineral metabolism; its deficiency causes growth retardation and skeletal deformities in children and osteomalacia and osteoporosis in adults. Hypovitaminosis D (vitamin D insufficiency or deficiency) is observed not only in adults but also in infants, children, and adolescents. Previous studies suggest that sufficient serum vitamin D levels should be maintained in order to enhance normal calcification of the growth plate and bone mineralization. Moreover, emerging evidence supports an association between 25-hydroxyvitamin D (25[OH]D) levels and immune function, respiratory diseases, obesity, metabolic syndrome, insulin resistance, infection, allergy, cancers, and cardiovascular diseases in pediatric and adolescent populations. The risk factors for vitamin D insufficiency or deficiency in the pediatric population are season (winter), insufficient time spent outdoors, ethnicity (non-white), older age, more advanced stage of puberty, obesity, low milk consumption, low socioeconomic status, and female gender. It is recommended that all infants, children, and adolescents have a minimum daily intake of 400 IU (10 µg) of vitamin D. Since the vitamin D status of the newborn is highly related to maternal vitamin D levels, optimal vitamin D levels in the mother during pregnancy should be maintained. In conclusion, given the important role of vitamin D in childhood health, more time spent in outdoor activity (for sunlight exposure) and vitamin D supplementation may be necessary for optimal health in infants, children, and adolescents.